Une analyse structurale du rituel de la soirée électorale à la télévision - Richard Godin (Communication)
This paper consists of a structural functional analysis in which the author tackles a television broadcast of election night coverage from the angle of profane ritual. The analysis divides the broadcast into phrases and sequences before reconstructing it as a ritual. The objective is to extract from the analysis ritual signs connected to the hypothesis that election night coverage on television serves to structure the ordeal of passage which is the election of a man to the post of head of State. While coming to grips with the general and specific functions, the author teases out both the manifest and hidden structures linked to the ritual.